Association of ethnicity, Fitzpatrick skin type, and hirsutism: A retrospective cross-sectional study of women with polycystic ovarian syndrome - L. Afifi, MS; L. Saeed, BA; L.A. Pasch, PsyD; H.G. Huddleston, MD; M.I. Cedars, MD; L.T. Zane, MD, MAS; K. Shinkai, MD, PhD (Wolters Kluwer, 2017)
Background: The complex interplay between ethnicity, Fitzpatrick skin type (FST), and hirsutism in patients with polycystic ovarian syndrome (PCOS) is poorly understood. Objective: In this cross-sectional, retrospective analysis, we examined the prevalence, severity, and distribution of hirsutism with clinician-rated site-specific and total modified Ferriman-Gallwey (mFG) visual scoring in a diverse cohort of American patients with PCOS. Methods: Independent analyses were conducted on the basis of patient-reported FST ratings and ethnicity. Results: In this PCOS cohort, a correlation was found between hirsutism and ethnicity and the highest prevalence of hirsutism and total mFG scores was observed in Hispanic, Middle Eastern, African American, and South Asian patients. A positive correlation between hirsutism and FST was also observed with an increasing prevalence of hirsutism in the group of patients with higher FSTs. Significant trends in the anatomic distribution of hirsutism were observed between ethnic groups as well. A higher facial mFG score was found in African American patients but higher mFG scores in the truncal and extremity regions were observed in Middle Eastern patients. Truncal hirsutism was also associated with higher FSTs. Conclusions: Ethnicity and FST may be important variables in both the quantitative and qualitative presentations of hirsutism in women with PCOS and should be considered in the diagnostic evaluation of any patient who is suspected of having the condition. Previously published studies that examined ethnicity, FST, and hirsutism in homogeneous cohorts limited comparison and generalizability but the strength of this study lies in its detailed analysis within a single large and diverse PCOS cohort. Validated studies are needed to determine whether clinical criteria for hirsutism should be adjusted for ethnicity and FST in the PCOS population and particularly within diverse cohorts and patients of mixed ancestry. Keywords: PCOS, hirsutism, ethnicity, Fitzpatrick skin type, hyperandrogenism, modified Ferriman-Gallwey